Experimental research of neutron yield and spectrum from deuterium gas-puff Z-pinch on the GIT-12 generator at current above 2 MA; Energy Fluxes and Radiation Effects (EFRE-2016) - Cherdizov R. Rustam; Fursov F. I. Fedor; Kokshenev V. A. Vladimir; Kurmaev N. E. Nikolay; Labetsky A. Yu. Alexey; Ratakhin N. A. Nikolay Aleksandrovich; Shishlov A. V. Alexander; Cikhardt J. Jakub; Cikhardtova B. Balzhima; Klir D. Daniel; Kravarik J. Jozef; Kubes P. Pavel; et al. (2016, 2016)
Title screen